2006
DOI: 10.1096/fj.05-5568com
|View full text |Cite
|
Sign up to set email alerts
|

Methionine restriction decreases mitochondrial oxygen radical generation and leak as well as oxidative damage to mitochondrial DNA and proteins

Abstract: Previous studies have consistently shown that caloric restriction (CR) decreases mitochondrial reactive oxygen species (ROS) (mitROS) generation and oxidative damage to mtDNA and mitochondrial proteins, and increases maximum longevity, although the mechanisms responsible for this are unknown. We recently found that protein restriction (PR) also produces these changes independent of energy restriction. Various facts link methionine to aging, and methionine restriction (MetR) without energy restriction increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
191
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(206 citation statements)
references
References 43 publications
(56 reference statements)
12
191
2
1
Order By: Relevance
“…This supports previous evidence for the role of oxidative stress in aging (28)(29)(30)(31)(32) and contributes to a growing body of evidence suggesting that methionine abundance regulates the pathways that protect the cell from the ravages of oxidative metabolism. In higher organisms, methionine restriction has been found to increase longevity and reduce oxidative damage to proteins and mitochondrial DNA and to decrease ROS generated in the mitochondria (32).…”
Section: Role Of Mitochondrial Function and Stress Response In Starvasupporting
confidence: 88%
“…This supports previous evidence for the role of oxidative stress in aging (28)(29)(30)(31)(32) and contributes to a growing body of evidence suggesting that methionine abundance regulates the pathways that protect the cell from the ravages of oxidative metabolism. In higher organisms, methionine restriction has been found to increase longevity and reduce oxidative damage to proteins and mitochondrial DNA and to decrease ROS generated in the mitochondria (32).…”
Section: Role Of Mitochondrial Function and Stress Response In Starvasupporting
confidence: 88%
“…Interestingly restriction of methionine intake (40% and 80% restriction) has also been shown to decrease mitochondrial ROS generation and percent free radical leak in rat liver mitochondria (Caro et al, 2008). The same group also reported that protein restriction alone could decrease mitochondrial ROS production and mtDNA damage in rat liver (Sanz et al, 2004). Caloric restriction also retards age related diseases, studies of dietary links to Parkinson's disease and Alzheimer's suggest that individuals with a low calorie intake are at reduced risk (Matteson et al, 2002).…”
Section: Ros and Agingmentioning
confidence: 93%
“…Such oxidation affects biological activity as shown by loss of ␣ 1 -antitrypsin inhibitor activity upon Met oxidation (22). Two types of methionine sulfoxide reductases act on the structurally distinct S-and R-sulfoxides (65,89,196); methionine sulfoxide reductases activities are dependent on thioredoxins (Trx) (196) and have been associated with longevity (123,130,147,152). The less common selenol of Sec undergoes reversible oxidation-reduction during catalytic functions of Trx reductases and Se-dependent GSH peroxidases (52,96).…”
Section: The Redox Hypothesismentioning
confidence: 99%